Modeling Ewing Sarcoma Lung Metastasis. Issue 2 (17th February 2023) - Dasgupta, Atreyi; Kurenbekova, Lyazat; Patel, Tajhal D.; Rajapakshe, Kimal; Ghosal, Gargi; Nirala, Bikesh; Coarfa, Cristian; Yustein, Jason
Abstract: Ewing Sarcoma (EwS) is the second most common malignant bone tumor in adolescents and young adults. The single‐most powerful predictor of outcome in EwS is presence of metastatic burden at the time of diagnosis. Patients with metastatic Ewing Sarcoma have an abysmal 5‐year survival rate of 10%‐25%, which has not changed over the past 30‐40 years. Thus, unraveling underlying mechanisms of EwS metastasis are imperative for developing effective therapeutic measures. Investigations towards this goal are limited by the lack of reliable genetically engineered mouse models and specialized metastatic models. Using two established cell lines, A673 and TC71, we generated lung specific metastatic cell lines by serial orthotopic intra‐tibial injection followed by isolation of cells from lung metastases. The lung metastatic lines generated exhibit distinct differential molecular signatures from the parental cells when analyzed using a multi‐omics approach. These signatures overlapped with EwS patient primary bone and metastatic lung specimens supporting the clinical relevance of these preclinical models of EwS. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Intra‐Tibial injection in NSG mice Basic Protocol 2 : Development and characterization of lung metastatic cell line